2020
DOI: 10.21203/rs.2.20649/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incidence of Hypertension among Persons Living with HIV in China: A Multicenter Cohort Study

Abstract: Background Life expectancy among persons living with HIV (PLWH) has improved with increasing access to antiretroviral therapy (ART), however incidence of chronic comorbidities has simultaneously increased. No data are available regarding the incidence of hypertension among Chinese PLWH. Methods We analyzed data collected from patients enrolled in two prospective longitudinal multicenter studies of PLWH initiating ART in China. Incidence rate of hypertension per 100 person-years (PYs) among PLWH was calculat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…[42] A large number of studies have been published during the past 5 years worldwide on the effect of aging with HIV on non-AIDS associated comorbidities. [43][44][45][46][47] Data from the United States (US) showed that the prevalence of multimorbidities (≥2) among a cohort of more than 22,900 of PLHIV increased from 8% to 22% during a 9-year period of follow-up. [48] Hypertension and hypercholesterolemia were the most common co-occurred comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…[42] A large number of studies have been published during the past 5 years worldwide on the effect of aging with HIV on non-AIDS associated comorbidities. [43][44][45][46][47] Data from the United States (US) showed that the prevalence of multimorbidities (≥2) among a cohort of more than 22,900 of PLHIV increased from 8% to 22% during a 9-year period of follow-up. [48] Hypertension and hypercholesterolemia were the most common co-occurred comorbidities.…”
Section: Discussionmentioning
confidence: 99%